In Hospital Outcomes of Cardiogenic Shock among Patients with Acute Myocardial Infarction - Faheem Iqbal, Ujala Nazir, Fida Muhammad, Bilal Mustafa, Omer Saqib Gill, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate in-hospital cardiogenic shock (CS) outcomes after acute myocardial infarction. Study Design: A descriptive study. Place and Duration:InPunjab Institute of Cardiology, Lahorefor six-months duration from 18th June 2021 to 17th December 2021. Materials and Methods: After meeting the inclusion criteria, 200 consecutive patients with cardiogenic shock afterwardsthe acute myocardial infarction were studied. The major group was Group I consisting of 105 (52.5%) subjects; these were CS patients with STEMI. The patients of group-IIcomprised of 80 (40%) subjects, these were cases with CS with Non-STEMI and patients of the group III were 15 (7.5%); with acute left bundle branch block (LBBB) in the CS setting. Results: The mean age of the study people was 57.2 ± 29.40. The males in the studied people were 130 (65%), and women 70 (35%). In group I; 50 (47.6%) was the in-hospital mortality, group II has in-hospital mortality of 57 (71.3%) and in group III it was 7 (46.7%) cases. Conclusions: Patients who developed cardiogenic shock afterwardsacute myocardial infarction have high ratio of mortality during their stay in hospital. This is because there are more risk factors in this subset of patients.